PENGGUNAAN MEDIA ONLINE WHATSAPP DALAM AKTIVITAS KOMUNITAS ONE DAY ONE JUZ (ODOJ) DALAM MENINGKATKAN MINAT TILAWAH ODOJER DI KOTA PEKANBARU - Ariza Rusni; Elysa Evawani Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
More and more devices increasingly sophisticated technologies to communicate. This simplicity also be partly used to spread the goodness of people, such as preaching and invites every Muslim loves Alquran.One Day One Juz (ODOJ) is a program initiated by the House of Allah to facilitate and simplify the Muslims in order to familiarize recitations of the Koran one juz a day by using WhatsApp. Although relatively new, but this movement menjukkan rapid growth. Some lembagapun began introducing the One Day One Juz the mechanism a step further through advanced phones or WhatsApp. Seeing the enthusiastic community growing rapidly, in 2013 created the method through application WhatsApp.Similarly, the One Day One Juz community that uses social media and application WhatsApp as a tool to communicate to share information. With this application makes odoj community activities more effective because the admin is always burning spirit of the odojer to always bertilawah and understand the contents of the contents of the content of the al-Quaran. This study uses a qualitative method with phenomenological study as research design using the theory of S-O-R. Which is trying to give an explanation of the individual's experience in using WhatsApp as a medium to interact with one another who are members of this community.The results of this study theMember Odojer in the city of Pekanbaru utilizing WhatsApp application as a means of communication online, though now a lot of new applications that support these communities such as Blackberry Messenger and line to interact but the application WhatsApp still faithful hearts of odojer myriads pekanbaru. Activities tilawah a pleasure for administrators and other odojer remind each other to constancy bertilawah every day admin and PJH duty always greet odojer with words meyejukkan heart. Many positive activities carried odoj community as kalqulus, Olympics lover alqur'an.tilawah check ups, as well as donating provide food for scavengers and beggars.Keywords : Whatsapp Online Media, Community Activities Juz